The effect of polyploidy and hybridization on the evolution of floral colour in Nicotiana (Solanaceae) - McCarthy, Elizabeth W; Arnold, Sarah E J; Chittka, Lars; Le Comber, Steven C; Verity, Robert; Dodsworth, Steven; Knapp, Sandra; Kelly, Laura J; Chase, Mark W; Baldwin, Ian T; Kovařík, Aleš; Mhiri, Corinne; et al. (Annals of botany, 2015)
BACKGROUND AND AIMS: Speciation in angiosperms can be accompanied by changes in floral colour that may influence pollinator preference and reproductive isolation. This study investigates whether changes in floral colour can accompany polyploid and homoploid hybridization, important processes in angiosperm evolution. METHODS: Spectral reflectance of corolla tissue was examined for 60 Nicotiana (Solanaceae) accessions (41 taxa) based on spectral shape (corresponding to pigmentation) as well as bee and hummingbird colour perception in order to assess patterns of floral colour evolution. Polyploid and homoploid hybrid spectra were compared with those of their progenitors to evaluate whether hybridization has resulted in floral colour shifts. KEY RESULTS: Floral colour categories in Nicotiana seem to have arisen multiple times independently during the evolution of the genus. Most younger polyploids displayed an unexpected floral colour, considering those of their progenitors, in the colour perception of at least one pollinator type, whereas older polyploids tended to resemble one or both of their progenitors. CONCLUSIONS: Floral colour evolution in Nicotiana is weakly constrained by phylogeny, and colour shifts do occur in association with both polyploid and homoploid hybrid divergence. Transgressive floral colour in N. tabacum has arisen by inheritance of anthocyanin pigmentation from its paternal progenitor while having a plastid phenotype like its maternal progenitor. Potentially, floral colour evolution has been driven by, or resulted in, pollinator shifts. However, those polyploids that are not sympatric (on a regional scale) with their progenitor lineages are typically not divergent in floral colour from them, perhaps because of a lack of competition for pollinators.
Keywords: hybridizace genetická; pollinator shifts; biologická evoluce; Solanaceae; barva; transgressive traits; polyploidie; Flowers; Nicotiana; Polyploidy; polyploidy; pigmentace; Color; flower pigmentation; Hybridization, Genetic; Pigmentation; Evolution, floral colour; hybridization; spectral reflectance; Biological Evolution; tabák; květy